A Review on Tailored Blanks - Production, Applications and Evaluation - Merklein, Marion; Johannes, Maren; Lechner, Michael; Kuppert, Andreas (Journal of Materials Processing Technology, 2014)
Tailored Blanks is the collective for semi-finished sheet products which are characterised by a local variation of the sheet thickness, sheet material, coating or material properties. With these adaptions the tailored blanks are optimised for a subsequent forming process or the final application. In principle four different approaches can be distinguished to realise tailored blanks: joining materials with different grade, thickness or coating by a welding process (tailor welded blanks), locally reinforcing the blank by adding a second blank (Patchwork blanks), creating a continuous variation of the sheet thickness via a rolling process (tailor rolled blanks) and adapting the material properties by a local heat treatment (tailor heat treated blanks). The major advantage of products made from tailored blanks in comparison to conventional products is a weight reduction. This paper covers the state of the art in scientific research concerning tailored blanks. The review presents the potentials of the technology and chances for further scientific investigations. © 2013 Elsevier B.V.
LFT Import::2019-07-29 (1911)
Keywords: Forming; Patchwork blanks; Tailor heat treated blanks; Tailor rolled blanks; Tailor welded blanks; Tailored blanks

Fabrication of three-dimensional photonic crystals with tunable photonic properties by biotemplating - Van Opdenbosch, Daniel; Johannes, Maren; Wu, Xia; Fabritius, Helge; Zollfrank, Cordt (Photonics and Nanostructures-Fundamentals and Applications, 2012)
Photonic crystals with tunable D-surface structures for possible high-temperature gas- and temperature-sensing applications were prepared by a biotemplating method. This included infiltrating colored scales of the beetle Entimus imperialis with an organopolysiloxane mixture followed by simultaneous combustion of the template and calcination of the cured organopolysiloxane. A high-yield inorganic silica-based replica of the original structure was obtained, which is capable of withstanding temperatures up to 600 °C. Light- and scanning electron microscopy combined with focused ion beam milling showed a precise replication of the whole scales and their internal D-surface structure. Fourier-transform infrared spectroscopy and X-ray diffraction analysis confirmed the complete curing of the organopolysiloxanes and their transformation into amorphous silica during calcination. The dielectric constant of the manufactured materials determined by Abbé refractometry was ε = 2.3180 and used to perform band structure calculations utilizing the plane wave expansion method. By changing the chain length and degree of crosslinking of the organopolysiloxane precursor mixture, the lattice parameters and filling factors, and therefore the photonic properties of the replicas, could be tuned. © 2012 Elsevier B.V. All rights reserved.
LFT Import::2019-07-29 (1810)
Keywords: Biotemplating; D-surface; Inorganic; Photonic; Sensing application; Tunable

Influence of Pre-straining and Heat Treatment on the Yield Surface of Precipitation Hardenable Aluminum Alloys - Lechner, Michael; Johannes, Maren; Kuppert, Andreas; Merklein, Marion (Physics Procedia, 2014)
LFT Import::2019-07-29 (2045)
Keywords: Aluminum; Intermediate heat treatment; Yield surface

Numerical optimisation of a shear specimen geometry according to ASTM - Merklein, Marion; Hofmann, Maren; Biasutti, Manfredi; Lechner, Michael (Key Engineering Materials, 2013)
Complex material models used for the numerical representation of forming processes need in addition to tension and compression tests also shear tests to completely analyse the behaviour of the material under different loading conditions. There are two concepts of shear test - one uses symmetrical specimens with two shear zones (according to Miyauchi) the other one specimens with a single shear zone. In both cases, a homogeneous distribution of the strain in the shear zone is essential for the validity of the shear test. Therefore, the length and width of the shear zone in a single shear specimen made from high strength steel according to the ASTM standard geometry were varied. Analysing the resulting strain distribution numerically an optimised sample geometry with a more uniform strain distribution than the ASTM standard was achieved. The numerical results were also validated with experimental shear tests. © (2013) Trans Tech Publications.
LFT Import::2019-07-29 (1857)
Keywords: ASTM specimen geometry; Numerical optimisation; Simple shear test

Über die Blechprüfung von heute - Merklein, Marion; Suttner, Sebastian; Hofmann, Maren; Kuppert, Andreas (Tagungsband Werkstoffprüfung, 2012)
LFT Import::2019-08-05 (1839)